2021
DOI: 10.1128/msystems.00903-20
|View full text |Cite
|
Sign up to set email alerts
|

Engineering High-Yield Biopolymer Secretion Creates an Extracellular Protein Matrix for Living Materials

Abstract: The bacterial extracellular matrix forms autonomously, giving rise to complex material properties and multicellular behaviors. Synthetic matrix analogues can replicate these functions but require exogenously added material or have limited programmability. Here, we design a two-strain bacterial system that self-synthesizes and structures a synthetic extracellular matrix of proteins. We engineered Caulobacter crescentus to secrete an extracellular matrix protein composed of an elastin-like polypeptide (ELP) hydr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 83 publications
0
25
0
Order By: Relevance
“…First of all, protein production must be coupled with secretion so that PBMs can assemble in the extracellular space and create a matrix. Compared 12 The panel showing the seeded chain-growth polymerization was adapted with permission from Bowen et al 7 The panel showing the optimization of protein secretion is from Orozco-Hidalgo et al 13 ll Matter 4, 3095-3120, October 6, 2021 3099 with intracellular expression, exporting proteins outside of the cell is an onerous task. Protein secretion or translocation to the cell membrane is crucial for myriad processes in bacterial physiology, such as pathogenicity, membrane homeostasis, nutrition, and protection.…”
Section: Challenge 1: Controlling Secretion and Assembly To Deliver Engineerable Protein-based Elmsmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, protein production must be coupled with secretion so that PBMs can assemble in the extracellular space and create a matrix. Compared 12 The panel showing the seeded chain-growth polymerization was adapted with permission from Bowen et al 7 The panel showing the optimization of protein secretion is from Orozco-Hidalgo et al 13 ll Matter 4, 3095-3120, October 6, 2021 3099 with intracellular expression, exporting proteins outside of the cell is an onerous task. Protein secretion or translocation to the cell membrane is crucial for myriad processes in bacterial physiology, such as pathogenicity, membrane homeostasis, nutrition, and protection.…”
Section: Challenge 1: Controlling Secretion and Assembly To Deliver Engineerable Protein-based Elmsmentioning
confidence: 99%
“…28 However, type I secretion systems export only partially or fully unfolded proteins. To secrete proteins with folded domains, Orozco-Hidalgo et al 13 took the innovative approach of swapping the folded domain with a mutant version that folds slowly. This boosted the yield from undetectable levels to $60 mg L À1 , the highest yield of a secreted biopolymer by a type I secretion system.…”
Section: Challenge 1: Controlling Secretion and Assembly To Deliver Engineerable Protein-based Elmsmentioning
confidence: 99%
“…In a recent study, the same group engineered C. crescentus to produce a crosslinked extracellular protein matrix for living materials [ 220 ]. To this aim, C. crescentus was engineered to secrete via its type-1 secretion apparatus an extracellular matrix protein constructed from elastin-like polypeptides fused to a supercharged SpyCatcher variant.…”
Section: Elmsmentioning
confidence: 99%
“…It was shown that this secreted protein bound covalently to a SpyTag-functionalized S-layer (see paragraph above) of C. crescentus . This two-strain system to secrete a synthetic extracellular protein matrix was suggested as a step toward understanding the parameters required to engineer living cells to autonomously construct ELMs [ 220 ].…”
Section: Elmsmentioning
confidence: 99%
“…True ELMs have been created by engineering E. coli to produce an extracellular matrix from curli fibers 825 . Other types of extracellular matrices for ELM fabrication were created from secreted bacterial cellulose to embed microbial cells 26, 27 or from elastin-like polypeptides to attach Caulobacter cells via their protein S-layers 28 . Among these examples, the secretion of a polypeptide-based scaffolding system or matrix offers greater control over material assembly and functionalization due to the genetic programmability of polypeptide structures and functions.…”
Section: Introductionmentioning
confidence: 99%